Emotional burnout and professional deformations of educators in inclusive education - Ральникова, Ирина; Савельева, Татьяна (Pedagogy and Psychology, 2021)
The article presents the results of studying the emotional burnout and professional deformations of pedagogical workers (pedagogical psychologists, speech therapists, social pedagogues) in the inclusive sphere of education as related phenomena. Professional deformations of pedagogical workers objectify themselves by pronounced authoritarianism, uncritical thinking, rigidity in behavior. Pedagogical workers with professional deformations have the formed emotional burnout syndrome, which is represented by a high level of emotional tension in the phases of resistance, tension and exhaustion. The dominant symptoms of burnout syndrome were "experiencing traumatic circumstances", "anxiety", "inadequate emotional response", "economy of emotions", "reduction of professional duties", "personal detachment". Symptoms such as “dissatisfaction with oneself”, “being caged into a cage”, “emotional disorientation”, “emotional deficit”, “emotional alienation”, “psychosomatic and psychoemotional disorders” are clearly expressed, but there are stages of formation. Expressed authoritarianism, high rigidity, reduced criticality and reflexivity act as signs associated with emotional burnout of teachers accompanying the education and development of children with disabilities.